Navigating geopolitical risks: How U.S. firms adjust supply chains amid U.S.–China rivalry - Yang, Bo; Song, Jinyuan; Wei, Yifan; Li, Jing (Journal of International Business Studies, 2025)
We investigate how U.S. firms adapt their supply chains in China in response to geopolitical risks from the U.S.–China rivalry. We offer a legitimacy-efficiency balancing perspective to understand firm decisions. We hypothesize that to maintain legitimacy with the home government, U.S. firms in strategic industries are more likely than those in non-strategic industries to align with the U.S. government’s derisking strategy by limiting suppliers in China. However, we expect this tendency to weaken for firms with high economic dependence on China. Analyzing firm-level supplier data from 2009 to 2022, we find that the gap in the number of Chinese suppliers between strategic and non-strategic U.S. firms has widened since 2017 (the first Trump administration). Firms in strategic industries maintain fewer Chinese suppliers, potentially reflecting a more cautious approach. This disparity was initially pronounced only among Republican-leaning firms but later extended to firms across the political spectrum under the Biden administration. The gap diminished among firms with greater reliance on China for revenue or supplies, suggesting that efficiency considerations might temper the inclination to align with national strategies. Thus, U.S. firms might seek to balance political legitimacy at home with the economic benefits derived from China when making supplier decisions.